Adult attention-deficit/hyperactivity symptoms and parental cognitions: a meta-analysis - Miklósi, Mónika; Kovács, Barbara; Janovicz, Júlia; Lelki, Franciska; Kassai, Réka (Frontiers in Psychiatry, 2024)
Introduction Attention-deficit/hyperactivity disorder (ADHD) symptoms in adults interfere with parental functioning. Dysfunctional parental cognitions may play a role in this impairment. Despite the importance of parental cognitions on parents and children’s outcomes, up to now, no systematic review or meta-analysis of these findings is available. To fill this gap, this meta-analysis aimed to evaluate the relationship between adult ADHD symptoms and parental cognitions. Methods We conducted searches in Web of Science, PubMed, and ProQuest from January 2000 to June 2023. Studies were included if they provided data on the relationship between parental ADHD symptoms and parental cognitions by means of a row correlational coefficient, or means and standard deviation were reported for each study group. A random-effects model was used. Publication bias was assessed by funnel plot and Rosenthal’s fail-safe N. Moderator analyses were conducted by means of subgroup analysis and meta-regression analyses. Results Fifteen published papers were included (N = 2851), and 51 effect sizes were analysed. The weighted mean effect size was small but significant (Fisher’s Z = 0.186, k = 15, 95% CI [0.120 – 0.252], z = 5.539, p < 0.001), indicating that ADHD symptoms in adults are associated with more negative and less positive parental cognitions. The Fail-Safe N analysis suggested a robust effect. Tweedie’s trim and fill results suggested that five studies were missing; after five missing studies had been imputed, the mean overall effect size dropped to 0.116 (0.080 – 0.152). There was significant heterogeneity among effect sizes. The methodology of the study was found to be a significant moderator. Meta-regression analyses revealed that the lower age of the parent and the child were related to more negative parental cognitions. Discussion Though the analysis might be inflated by publication bias, our results suggest a significant association between ADHD symptom level and dysfunctional parental cognitions. Biased negative perceptions of the parental role, the child and co-parenting may play a central mediator role between parental ADHD and parent and child outcomes. Given the familiar nature of ADHD, targeting dysfunctional parental cognitions in parent training programs is warranted. Systematic review registration osf.io/pnur7.